Valorization of fruit waste from Cucurbitaceae family: Profiling of phytoconstituent of Benincasa hispida and Citrullus lanatus rinds using ultrasound-assisted extraction. (February 2023) - Yusoff, Ida Madiha; Chua, Lee Suan; Taher, Zarani Mat
Abstract: Food agricultural waste from fruit products such as rinds can be one source of environmental pollution. Therefore, the study was conducted to investigate the total phenolic content, total flavonoid content, antioxidant property, and chemical profiling using gas chromatography-mass spectrometer (GC-MS) and high-performance liquid chromatography tandem mass spectrometry of triple quadrupole (HP LCMS-MS QTOF). Ultrasound-assisted extraction for 45 min was used as a green technique to extract bioactive compounds from watermelon ( Citrullus lanatus ) and wintermelon ( Benincasa hispida ) rinds. The total phenolic content and total flavonoid content of ultrasound-assisted extraction were compared with maceration technique. As revealed by the results, maceration technique had a lower total phenolic content for both C. lanatus rind (7.07 ± 0.86 μg GAE/mg) and B. hispida rind (13.87 ± 0.11 μg GAE/mg) compared to ultrasound-assisted extraction. The similar trends can be observed in total flavonoid content of C. lanatus rind (4.97 ± 0.29 μg RE/g) and B. hispida rind (8.30 ± 0.17 μg RE/g) by maceration which showed a lower quantity compared to ultrasound-assisted extraction. The ultrasound-assisted extraction was selected for further analysis. The total phenolic content assay found that the B. hispida rind extract exhibited higher total phenolic content values (23.39 ± 0.22 μg GAE/mg), than C. lanatus rind extract (15.10 ± 0.58 μg GAE/mg). B. hispida rind extract had a higher total flavonoid content (11.17 ± 0.17 μg RE/g) than C. lanatus rind extract (6.16 ± 0.09 μg RE/g). The antioxidant activity was investigated using DPPH scavenging assay. The antioxidant capacity of B. hispida rind extract (20872.19 ± 1301.47 mg/mL) stronger compared to C. lanatus rind extract (23514.47 ± 678.70 mg/mL). Results revealed that there was a negative correlation between total phenolic content, total flavonoid content, and DPPH scavenging activity IC50. The phytoconstituent determination in B. hispida and C. lanatus rind extract showed both contained phenolic, malic acid, and other compounds that might have contributed to antioxidant activities. Phenolic, flavonoid, and antioxidant activities are useful to valorize B. hispida and C. lanatus rinds as they can be converted into new income-generating resources in agriculture and the food industry. Graphical abstract: Image 1 Highlights: Fruit rinds from Benincasa hispida and Citrullus lanatus are important sources for phenolic and flavonoid compounds. Ultrasound-assisted extraction enhanced compound extraction and scavenging activities compared to maceration. Ultrasound technology is a useful green technology to utilize fruit rinds into functional products. Negative correlation between phenolic, flavonoid with DPPH scavenging activity IC50 .